The precautionary principle a rose by another name [cellular radio health effects]. - Lin, James C. (IEEE Antennas & propagation magazine.)
The number of cellular mobile telephone subscribers worldwide is in the 100s of millions, and is increasing at a rate of about 2% per month. The market penetration is well above 80% in some territories. Nevertheless, the potential health effects of radio frequency (RF) and microwave radiation, associated with cellular mobile telephones and related wireless devices, remain a leading cause of concern among users. While the scientific evidence on biological effects of RF and microwave radiation associated with these wireless devices is still tentative, the precautionary principle seems to be dominating the debate outside the United States, especially in Europe. The precautionary principle is a tool that may be used to guide decision making, where potential risks to human health and the environment require the adoption of an appropriate policy. The essence of the principle is captured in notions such as common sense or safety margins: a rose by another name? It is believed that the precautionary approach can enable individuals and societies to manage potential risks without departing from the principles of sound science, and in a way that is non-arbitrary and satisfactory in the eyes of public opinion. Such an approach can be of appreciable benefit; as human experiences show, it also can be of dubious utility and may even be counterproductive, depending on how it is applied.